2002
DOI: 10.1105/tpc.000869
|View full text |Cite
|
Sign up to set email alerts
|

The Homologous ABI5 and EEL Transcription Factors Function Antagonistically to Fine-Tune Gene Expression during Late Embryogenesis

Abstract: In Arabidopsis, the basic leucine zipper transcription factor ABI5 activates several late embryogenesis-abundant genes, including AtEm1 and AtEm6 . However, the expression of many other seed maturation genes is independent of ABI5 . We investigated the possibility that ABI5 homologs also participate in the regulation of gene expression during seed maturation. We identified 13 ABI5 -related genes in the Arabidopsis genomic sequence. RNA gel blot analysis showed that seven of these genes are active during seed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
235
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(247 citation statements)
references
References 50 publications
10
235
0
Order By: Relevance
“…Since ABRE2 mutation almost abolishes GUS expression, this element appears to be the most important by itself. Considering that the mutations introduced in ABRE and RY boxes have been shown to abolish the binding of bZIP and B3 domain transcription factors, respectively (Reidt et al, 2000;Bensmihen et al, 2002), these results suggest that transcription factors from these families may be directly involved in SDH2-3 regulation. .…”
Section: Sdh2-3 Expressionmentioning
confidence: 84%
“…Since ABRE2 mutation almost abolishes GUS expression, this element appears to be the most important by itself. Considering that the mutations introduced in ABRE and RY boxes have been shown to abolish the binding of bZIP and B3 domain transcription factors, respectively (Reidt et al, 2000;Bensmihen et al, 2002), these results suggest that transcription factors from these families may be directly involved in SDH2-3 regulation. .…”
Section: Sdh2-3 Expressionmentioning
confidence: 84%
“…The double blue lines indicate protein interaction (ABI3-ABI5 [Nakamura et al, 2001] and L1L-bZIP67 [Yamamoto et al, 2009]). Regulation of AtEM1 and AtEM6 (Bensmihen et al, 2002), of ABI5 (Lopez-Molina et al, 2002, and of fatty acid biosynthesis genes (Maeo et al, 2009) is also shown. Yellow, B3 domain; purple, basic Leu zipper; pink, AP2 related; orange, AUXIN RESPONSIVE/INDOLE-3-ACETIC ACID INDUCIBLE (IAA); blue, NFYB/HEME-ACTIVATED PROTEIN3; mint, zinc finger; green, MADS.…”
Section: Fus3 and Genes Regulated In Response To Supraoptimal Temperamentioning
confidence: 90%
“…TES, Transcriptional end site; TSS, transcriptional start site; up/down 1 kb, within 1 kb of the TSS and/or TES as indicated; UTR, untranslated region of the transcript 59 and 39 of the coding sequences (CDS) that will be translated to protein. A number of genes involved in embryogenesis were bound by FUS3 in the ChIP-chip experiment, including genes encoding the MADS domain transcription factor AGL15 (Heck et al, 1995), the LOB domain factor LBD40 (Shuai et al, 2002;Husbands et al, 2007), three LEC genes, LEC1, L1L, and FUS3 (Meinke et al, 1994;Lotan et al, 1998;Kwong et al, 2003), three B3 domain factors, FUS3, ABI3, and VAL1 (Giraudat et al, 1992;Luerssen et al, 1998;Tsukagoshi et al, 2005;Suzuki et al, 2007), the ABI5-like factor ENHANCED EM LEVEL (EEL; Bensmihen et al, 2002), and the AP2 family factor BBM (Boutilier et al, 2002;Supplemental Table S1). Enrichment tests were used to verify that sequences corresponding to these genes were truly occupied in vivo by FUS3.…”
Section: Genome-wide Identification Of In Vivo Binding Sites For Fus3mentioning
confidence: 99%
“…A gene similar to the Arabidopsis aldehyde oxidase (AAO2) that catalyzes the conversion of abscisic aldehyde into ABA (Leydecker et al, 1995;Seo et al, 2000) was reduced approximately 4-to 6-fold in phyB-1 buds relative to the corresponding wild-type controls at all time points. A gene encoding abscisic acid 89-hydroxylase (Sb02g026600.1) that deactivates ABA, and a protein phosphatase 2C (ABI1, Sb09g022410.1) that is a negative regulator of ABA signaling (Gosti et al, 1999;Bensmihen et al, 2002), were also expressed at a higher levels in phyB-1 buds. However, the expression of two ABA-inducible genes, Sb01g021730.1 (mediator of ABA-regulated dormancy1; He and Gan, 2004) and Sb05g017940.1 (HVA22-like; Shen et al, 2001), was higher in phyB-1 buds relative to the corresponding wild-type controls.…”
Section: Differential Expression Of Genes Involved In Plant Hormone Mmentioning
confidence: 99%